(untitled) (Eurasian Journal of Philology Science and Education, 2021)
In the article the intergenre changes in Azerbaijan folk-lore are investigated and the genre features of epic, lyrical and dramatic kinds are looking through. The genre and intergenre changes in Azerbaijan folk-lore are not learned enough. The appearance, stability of structure and the stages of intergenre changes of some regions are in need of investigation. Mugan region wich we have chousen for investigation of the theme is rich in various folk-lore samples. On this purpose to define the folk-lore area of the region and to investigate genre potential are very important. That is why seriously collecting and printing of folk-lore samples are the first stage of investigation. The intergenre changes of saga (dastan), tale (nağıl), joke, entifa (ağı) and other folklore spesimens are looking through. Intergenre changes prove the development characters of the genre. In fact, the talk is about the forms of genre. The studing and investigation of intergenre changes put an end on various thoughts on folk-lore and give the explanation that the folk-lore speimen which faced to changes is independent genre spesimen, or the kind of any genre. The author mostly supports on his own collection of folk-lore spesimens. It is noted that the theme is investigated for the first time.